A Prospective Study on the Incidence and Outcome of Cranial Nerve Injuries in Patients with Traumatic Brain Injuries - Basheer, Noufal; Varghese, Jenimol Chacko; Kuruvilla, Rojan; Alappat, Jacob P.; Mathew, Jim (Indian Journal of Neurotrauma, 2021)
Background Posttraumatic cranial nerve injuries are not uncommon and can occur by shearing forces, rapid acceleration/deceleration, or injury to the skull base. The incidence of cranial nerve injury in craniocerebral trauma varies between 5 and 23 percent in various literature.Methodology A prospective study was conducted on the incidence and outcome of cranial nerve injuries (CNI) in 256 consecutive cases of traumatic brain injuries (TBI). Patients over the age of 5 years with a follow-up of 6 months in the period from September 2017 to November 2018 in our institution were sampled.Results A total of 256 patients were included in our study. The incidence of CNI in TBI patients was 14.8% (38 patients). Facial nerve was the most common cranial nerve to be involved, followed by olfactory nerve and vestibulocochlear nerve. Cranial nerve injury was more common in patients with severe head injury (p < 0.005), younger age group, associated base of skull fractures (p < 0.001), and facial fractures (p < 0.005). Twenty-eight patients (73.7%) had a delayed presentation of CNI (p < 0.001). Of the 73.6% patients who recovered, 16 (42%) patients had partial recovery, while 12 (31%) patients had complete recovery. Younger age group (p < 0.05) and delayed onset of deficit (p < 0.001) were associated with significant better outcome.Conclusions CNI are a major cause of morbidity in TBI patients. All patients admitted with TBI should be examined meticulously for CNI on follow-up.
Keywords: head injury; cranial nerve; traumatic brain injury